Prognostic performance of the REDS score, SOFA score, NEWS2 score, and the red-flag, NICE high-risk, and SIRS criteria to predict survival at 180 days, in emergency department patients admitted with suspected sepsis – An observational cohort study - Sivayoham, Narani; Hussain, Adil N.; Sheerin, Thomas; Dwivedi, Prerak; Curpanen, Danalakshmee; Rhodes, Andrew (Frontiers in Medicine, 2023)
Background Patients admitted to hospital with sepsis are at persistent risk of poor outcome after discharge. Many tools are available to risk-stratify sepsis patients for in-hospital mortality. This study aimed to identify the best risk-stratification tool to prognosticate outcome 180 days after admission via the emergency department (ED) with suspected sepsis. Methods A retrospective observational cohort study was performed of adult ED patients who were admitted after receiving intravenous antibiotics for the treatment of a suspected sepsis, between 1st March and 31st August 2019. The Risk-stratification of ED suspected Sepsis (REDS) score, SOFA score, Red-flag sepsis criteria met, NICE high-risk criteria met, the NEWS2 score and the SIRS criteria, were calculated for each patient. Death and survival at 180 days were noted. Patients were stratified in to high and low-risk groups as per accepted criteria for each risk-stratification tool. Kaplan–Meier curves were plotted for each tool and the log-rank test performed. The tools were compared using Cox-proportional hazard regression (CPHR). The tools were studied further in those without the following specified co-morbidities: Dementia, malignancy, Rockwood Frailty score of 6 or more, long-term oxygen therapy and previous do-not-resuscitate orders. Results Of the 1,057 patients studied 146 (13.8%) died at hospital discharge and 284 were known to have died within 180 days. Overall survival proportion was 74.4% at 180 days and 8.6% of the population was censored before 180 days. Only the REDS and SOFA scores identified less than 50% of the population as high-risk. All tools except the SIRS criteria, prognosticated for outcome at 180 days; Log-rank tests between high and low-risk groups were: REDS score p < 0.0001, SOFA score p < 0.0001, Red-flag criteria p = 0.001, NICE high-risk criteria p = 0.0001, NEWS2 score p = 0.003 and SIRS criteria p = 0.98. On CPHR, the REDS [Hazard ratio (HR) 2.54 (1.92–3.35)] and SOFA [HR 1.58 (1.24–2.03)] scores out-performed the other risk-stratification tools. In patients without the specified co-morbidities, only the REDS score and the SOFA score risk-stratified for outcome at 180 days. Conclusion In this study, all the risk-stratification tools studied were found to prognosticate for outcome at 180 days, except the SIRS criteria. The REDS and SOFA scores outperformed the other tools.